Materials design for ceramic oxygen permeation membranes: Single perovskite vs. single/double perovskite composite, a case study of tungsten-doped barium strontium cobalt ferrite - Zhang, J.; Zhang, Z.; Chen, Y.; Xu, X.; Zhou, C.; Yang, G.; Zhou, W.; Shao, Zongping (Elsevier BV, 2018)
© 2018 Elsevier B.V. Pure oxygen is an important raw material with many important applications. The production of oxygen via a conducting ceramic membrane is a new, cost-effective and advanced technology with the advantage of continuous oxygen production. The perovskite-type mixed-conducting oxide Ba0.5Sr0.5Co0.8Fe0.2O3-d (BSCF) exhibits superb oxygen permeability, yet it suffers from poor phase stability. In this study, we aim to improve the operational stability of the BSCF membrane by introducing a high-valence W6+ ion as a B-site dopant. Its effect on the phase composition, structure, structural stability, electrical conductivity, oxygen transfer rate and oxygen permeability as a membrane is systematically investigated. Upon the partial substitution of cobalt and iron in the W6+-doped BSCF, single/double perovskite composites are formed instead of single perovskite composites. Remarkably, the formation of the single/double perovskite composites enhances the oxygen permeation stability without obviously compromising the oxygen permeability. Among the various materials, the composite with the nominal composition of Ba0.5Sr0.5Co0.8Fe0.1W0.1O3-d shows the best performance in terms of stability and oxygen permeability. These findings thus introduce a new way to design conducting ceramic membranes for oxygen separation at high temperatures.